Ukrainian neopatrimonial democracy: dominant party-building and inter-elite settlement in the semi-presidential system - Fisun, O.; Polishchuk, A. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The effects of constitutional and electoral changes on the process of dominant party building during the presidency of V. Yanukovych are considered. The major competition strategies among interest groups of the party in power are defined in the context of Ukrainian neopatrimonial democracy. On the example of the 2012 election key cases of inter-elite struggle in the single-member districts are examined.